2017
DOI: 10.4172/2469-9837.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Body Image Perception in Association with Healthy Lifestyle Behaviour's in Lebanese Men and Women

Abstract: Background: Body image is an individual's self-perceptions and attitudes about his or her physical appearance, leading to either satisfaction or dissatisfaction. These self-perceptions can affect lifestyle of both men and women of all ages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
2
7
0
3
Order By: Relevance
“…This implied that student"s perception about their physical appearance and how they value themselves have a trivial effect on how they behave towards their health. The finding agrees with that of Moustafa et al (2018) who concluded that the relationship between body satisfaction and health behaviours was not strong due to the fact that health behaviour is a multifactorial construct that depends on many factors other than body image and self-esteem.…”
Section: Discussionsupporting
confidence: 90%
“…This implied that student"s perception about their physical appearance and how they value themselves have a trivial effect on how they behave towards their health. The finding agrees with that of Moustafa et al (2018) who concluded that the relationship between body satisfaction and health behaviours was not strong due to the fact that health behaviour is a multifactorial construct that depends on many factors other than body image and self-esteem.…”
Section: Discussionsupporting
confidence: 90%
“…The size of the present sample ( N = 561) is one of the largest samples in the literature to demonstrate a link between male body-esteem and health-related behaviors to date. The present findings provide further evidence of the relationship between body-esteem and health-related behaviors (Moustafa et al, 2017; Zanon et al, 2016).…”
Section: Discussionsupporting
confidence: 73%
“…Psychological research on the influence of health-related behaviors on body-esteem almost exclusively relied on nonvalidated surveys rather than validated measures of health-related behaviors ( Zanon et al, 2016 ). Few studies attempted to control for the impact of anthropometric measures, such as body mass index (BMI; e.g., Moustafa et al, 2017 ). Although males tend to exhibit a process-oriented view of their bodies, research identified that being overweight or obese might be a predictor of a desire to reduce weight and change appearance ( Bassett-Gunter et al, 2017 ; Page & Fox, 1997 ).…”
Section: The Relationship Between Health-related Behaviors and Body-ementioning
confidence: 99%
“…A satisfação com a imagem corporal tem uma forte influência no bem-estar mental (GESTSDOTTIR et al, 2017) e a insatisfação com a imagem corporal influência o desenvolvimento de perturbações alimentares dos adolescentes e adultos emergentes(SHAGAR et al, 2018).Um estudo de SILVA et al (2018) revelou uma associação entre a insatisfação com a imagem corporal e uma autoavalição menos positiva da saúde, podendo esta avaliação ser mediada direta, ou indiretamente, pelo sendentarismo e hábitos alimentares pouco saudáveis. Apesar da relação entre a satisfação com a imagem corporal e os estilos de vida saudáveis serem alvo de pouca investigação, o exercicio fisico pode ser essencial à perceção mais positiva da imagem corporal(MOUSTAFA et al, 2017).METODOLOGIAElencadas as questões de investigação e definidos os objetivos procedeu-se à seleção da metodologia mais adequada ao estudo e optámos por uma metodologia exploratória e quantitativa (RIBEIRO, 2010; SAMPIERI; COLLADO; LUCIO, 2013), por ser a mais adequada ao estudo.…”
unclassified